RELATIONSHIP BETWEEN KINESTHETIC INTELLIGENCE ON SCORING ACCURACY PERFORMANCE FROM MOVEMENT IN YOUNG FOOTBALL PLAYERS - Hussain Suhail Mathkor Khalati (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Kinesthetic intelligence is one of the important paradigm shifts in cognitive psychology and influences the level of basic skills in football in general and the accuracy of scoring goals from movement for young players. Objectives. The aim of this study is to understand the relationship between kinesthetic intelligence and scoring accuracy in football based on movement in a sample of young players. Method. The researchers used a descriptive method, and the study sample consisted of 30 young players out of 35, all from the Al-Minaa Club in Basra Governorate. They were selected purposefully. This chapter also covers shooting accuracy tests in football from movement, main experiments, and statistical methods. Chapter three presents, discusses, and analyzes the results. Chapter four includes conclusions and recommendations. Results. The research results show a difference in arithmetic mean between kinesthetic intelligence (3.6) and score accuracy (8.9) of movements in soccer. The results indicate a significant relationship, considering the calculated value (T=5.125) is greater than the tabulated value (T=2.048).. Conclusion. In conclusion, the contribution of kinesthetic intelligence to shooting accuracy in football from movement among young players is significant. The researcher also concluded that bodily-kinesthetic intelligence is important for shooting accuracy from movement in football for young players, and indeed in various sports, particularly football.